Professor Malcolm Mason: What could we do against cancer? - Xu, Eunice X.; Jiang, Yongshi (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
During the 9th National Gastric Cancer Academic Conference in Beijing, June 28th, 2014, the editor of Chinese Journal of Cancer Research (CJCR) had the honor of meeting Professor Malcolm Mason from Cardiff University School of Medicine and invited him to share his expert opinions about cancer staging and treatment for prostate cancer, as well as his experience of serving as director for Wales Cancer Bank.